Enterprise, business-process and information systems modeling : 14th International Conference, BPMDS 2013, 18th International Conference, EMMSAD 2013, Held at CAiSE 2013, Valencia, Spain, June 17-18, 2013. Proceedings - Nurcan, Selmin (Lecture Notes in Business Information Processing, 2013)
This book contains the refereed proceedings of the 14th International Conference on Business Process Modeling, Development and Support (BPMDS 2013) and the 18th International Conference on Exploring Modeling Methods for Systems Analysis and Design (EMMSAD 2013), held together with the 25th International Conference on Advanced Information Systems Engineering (CAiSE 2013) in Valencia, Spain, in June 2013. The 15 full papers, two experience reports, and three idea papers accepted for BPMDS were selected from 54 submissions and cover a wide spectrum of issues related to business process development, modeling, and support. They are grouped into sections on innovative representations for knowledge-intensive processes; business process management in practice; analysis of business process models; model-based business process analysis; flexible business process management; improvement and change patterns; and process model repositories . The 10 full and 2 short papers accepted for EMMSAD were chosen from 27 submissions and focus on exploring, evaluating, and enhancing current information modeling methods and methodologies. They are grouped in sections on advanced modelling; capturing design knowledge; method engineering; modelling process; specialized modelling; and modelling experiences.